2017
DOI: 10.1161/atvbaha.117.309923
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Hypercholesterolemia Exacerbates Atherosclerosis Lesions in Offspring by Altering Metabolism of Trimethylamine-N-Oxide and Bile Acids

Abstract: Our findings suggest that maternal hypercholesterolemia may exacerbate the development of atherosclerosis in female offspring by affecting metabolism of trimethylamine-N-oxide and bile acids. These data could be explained by epigenetic alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…Consistent with this possibility, a recent study showed that female Apoe −/− mice with hypercholesterolemic mothers develop larger aortic root lesions compared with mice with normocholesterolemic mothers—an effect that was associated with TMAO levels in the offspring. 40 …”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this possibility, a recent study showed that female Apoe −/− mice with hypercholesterolemic mothers develop larger aortic root lesions compared with mice with normocholesterolemic mothers—an effect that was associated with TMAO levels in the offspring. 40 …”
Section: Discussionmentioning
confidence: 99%
“…For example, ApoE deficiency and postnatal exposure to hypercholesterolemic environment causes altered histone methylation patterns in the vasculature (Alkemade, et al, 2010). Recently, Trenteseaux et al (Trenteseaux, et al, 2017)evaluated the effect of perinatal hypercholesterolemia on atherosclerosis development in the offspring of ApoE−/− mice. The authors observed that perinatal hypercholesterolemia exacerbates atherosclerosis in their offspring by epigenetically modulating several genes implicated in the metabolism of trimethylamine-N-oxide and bile acids via DNA methylation (Trenteseaux, et al, 2017).…”
Section: Trans-generational Inheritance and Trained Immunitymentioning
confidence: 99%
“…These findings concurred with the results of a previous report demonstrating the deleterious effects of FMO3 expression in glucose tolerance in liver-specific insulin receptor knockout mice [ 92 ]. Additionally, another recent study demonstrated that maternal hypercholesterolemia exacerbates the development of atherosclerosis with a positive association of aortic lesion size with both TMAO levels and increased FMO3 mRNA expression [ 93 ]. Overall, these data strongly indicate a role for FMO3 in modulating lipid and glucose homeostasis in vivo in a dose-dependent manner and, in some cases, independently of TMA/TMAO formation.…”
Section: The Physiological Interaction Between Tmao and Hdl In Thementioning
confidence: 99%